THE TRAINING NEEDS OF HIGHER EDUCATION TEACHERS IN THE CONTEXT OF TEACHING LEARNING: CONTRIBUTIONS FROM ACTIVITY THEORY - Ferreira de Oliveira Umbelino, Patrícia (Revista Gênero e Interdisciplinaridade, 2023)
This paper deals with a theoretical study, to highlight the concept of needs and their relationship with the continuing education of technical and administrative staff of federal universities servers. In this sense, describes the Activity Theory, AN Leontiev, placing it as a valuable theoretical framework for the development of studies in this direction